2012
DOI: 10.1016/j.jvs.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Unusual course of an abdominal aortic aneurysm in a patient treated with chemotherapy for gastric cancer

Abstract: Most aortic aneurysms have a degenerative genesis and show a slow expansion over years. Only a few patients with a rapid progression of mycotic or inflammatory aneurysm during some weeks or months have been reported. We report a patient with a rapidly growing symptomatic infrarenal aneurysm with a maximal diameter of 53 mm, which developed over a 5-month period from a normal aorta and did not feature typical signs of degenerative, inflammatory, or mycotic aneurysm. The aneurysm was successfully treated by endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…Two other cases involved acute enlargement of an abdominal aortic aneurysm following chemotherapy with gemcitabine, cisplatin, docetaxel, and 5-FU [21,22]. Some chemotherapy drugs have vascular toxicity and induce cell apoptosis leading to loss of integrity of the vascular wall [19][20][21][22][23]. In the present case, the ITPA was diagnosed during nivolumab administration as second-line chemotherapy following S-1 as adjuvant chemotherapy and RAM plus PTX as first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Two other cases involved acute enlargement of an abdominal aortic aneurysm following chemotherapy with gemcitabine, cisplatin, docetaxel, and 5-FU [21,22]. Some chemotherapy drugs have vascular toxicity and induce cell apoptosis leading to loss of integrity of the vascular wall [19][20][21][22][23]. In the present case, the ITPA was diagnosed during nivolumab administration as second-line chemotherapy following S-1 as adjuvant chemotherapy and RAM plus PTX as first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…Two cases of pseudoaneurysm developing after FOLFIRI (irinotecan, leucovorin, 5-fluorouracil: 5-FU) combined with bevacizmab and FOLFOX (oxaliplatin, leucovorin, 5-FU) have been reported [19,20]. Two other cases involved acute enlargement of an abdominal aortic aneurysm following chemotherapy with gemcitabine, cisplatin, docetaxel, and 5-FU [21,22]. Some chemotherapy drugs have vascular toxicity and induce cell apoptosis leading to loss of integrity of the vascular wall [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that chemotherapy in the last 30 days is associated with a higher probability of treating patients affected by abdominal aortic aneurysms in emergency situations [5]. Other researchers have found a correlation between chemotherapy and rapid enlargement and rupture of aortic aneurysms [6–8]. Our patient has been treated for the last five months with cycles of azacitidine 75 mg/m 2 monthly; he complained of acute left thigh pain during the fifth cycle of treatment.…”
Section: Discussionmentioning
confidence: 76%
“…We can suppose that this chemotherapeutic agent may have played a role in the rapid expansion of the aneurysm until its rupture. A possible explanation has been suggested by Zanow et al [6]: Chemotherapy may induce a downregulation of the synthesis of collagen, elastin, and smooth muscular cells, and a stimulation of metalloproteases, and these combined effects could cause a rapid aneurysm enlargement. To the best of our knowledge, this is the first case of femoral artery aneurysm rupture likely to be associated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Scarce evidence suggests a correlation between malignancy, Chx and aneurysmal degeneration. 6,18 In these few case reports, 6,18 growth rate substantially exceeded the expected 0.11 cm expansion per year for aneurysms 3-3.9 cm 19 or 0.13 ± 0.15 cm per year for ectatic aortas between 2.5 and 2.9 cm. 20 Vascular specialists often face the challenge of managing patients with malignancies and concomitant AAA that require repair and several treatment strategies have been suggested.…”
Section: Discussionmentioning
confidence: 82%